Incomplete Contract and Divisional Structures - Te Bao; Yongqin Wang (Tinbergen Institute, 2009)
In this paper we want to analyze the internal divisional structure within an organi-zation in the framework of incomplete contract theory. We use the framework of Aghionand Tirole (1997) and define the managerial control structure as sequence of search.A key feature of this paper which differentiate it from other works in the literature isthat we add add an ex post bargaining phase in which the managers can agree on theproject which maximize their joint private benefit. Our model shows the share of co-operative surplus the managers can get from bargaining and their default pay off playsa key role in determining their search effort. When there is no spill over effect betweenthe agents' effort, internal separation is always dominated by internal integration withcontrol right assigned to the agent (manager) with high interest congruence with theprincipal (head quarter). When there are synergy effect and setup cost during integra-tion, the principal need to consider the cost-benefit trade offs as Riyanto (2000) suggests.But more importantly, the optimal divisional structure depends heavily on whether thebargaining is interest congruence enhancing (increase the interest congruence betweenagents and the principal) or destroying (decrease the interest congruence).
Keywords: D23; L22; 330; organizational form; divisional structure; incomplete contract; bargaining; Unternehmensorganisation; Organisationsstruktur; Verhalten in Organisationen; Unvollständiger Vertrag; Verhandlungstheorie; Theorie